EMPLOYEE PERFORMANCE: COMMUNICATION, GROUP COLLABORATION, LEADERSHIP AND MOTIVATION - Khasbulloh Huda; Rachmad Sholeh; Sugeng Eko Yuli Waluyo; Mohamad Johan Efendi (LPPM of NAROTAMA UNIVERSITY, 2023)
This study examines how communication, group collaboration, leadership, and motivation affect to employee performance. This study was conducted at the office of the ministry of religion in Mojokerto. This study used the validity and reliability test, classical assumption test, multiple linear regression test, partial t test, and f simultaneous test. communication, group collaboration, leadership and motivation all affect employee performance. Partially the variable group collaboration, leadership and motivation has a direct affect on employee performance, but communication does not.